Electrical and optical properties of p-type conductive NiO-Pt thin films. (17th March 2014) - Chen, S.C.; Kuo, T.Y.; Lin, H.C.; Hsu, S.W.; Lin, Y.C.
In this work, we deposited NiO-Pt composite films with varying Pt content in the range of 0–25.83 at.%. An ultra high electrical resistivity ( ρ ) is obtained and cannot be detected by four point probe measurement when the Pt content in NiO films is lower than 1.46 at.%. As the Pt content in the films rises to 4.65 at.%, the ρ value can be reduced to 33.40 Ω cm, and it decreases significantly to 0.01 Ω cm when the content of Pt increases to 13.06 at.%. Upon further increasing the Pt content to 25.83 at.%, the ρ value of the film further decreases to 9.70 × 10 –4 Ω cm. The Hall measurement for all Pt-doped NiO films with Pt contents of above 4.65 at.% show p-type conduction. It is also found that the degree of crystallinity degrades in the films that have higher Pt contents. Furthermore, the transmittance of pure NiO film without adding Pt atoms is as high as 96%. When the Pt content in the films increases to 4.65 at.% and 25.83 at.%, it drops greatly to 55% and 21%, respectively.